Konflik Norma Hukum pada Pelayanan Hak Tanggungan Elektronik - Ameylia, Inge; Alfarico De Jesus, Marcello; Prameswari, Ristantia (JURNAL MINUTA, 2025)
Mortgage Rights Services have undergone significant changes in their registration process. This has led to a conflict of legal norms in the implementation of Electronic Mortgage Rights Services (HT-El) in Indonesia, especially regarding the dualism in the registration process involving Land Deed Officials (PPAT) and creditors. This study uses a normative-empirical legal approach by combining analysis of laws and regulations. The transition from conventional procedures as stipulated in Law No. 4 of 1996 concerning Mortgage Rights to a fully digital system through Permen ATR/BPN No. 9 of 2019 and No. 5 of 2020 has resulted in inconsistencies in norms and legal uncertainty. Although HT-El is expected to increase efficiency, transparency, and accessibility, this system raises issues related to dualism of roles, data security, and the legal force of electronic documents. This study identifies the main conflicts in the roles of PPAT and creditors, the validity of electronic signatures, and the legal standing of certificates issued digitally. System changes also pose risks in the priority of mortgage rights and the implementation of collateral execution due to the lack of synchronization between old laws and new regulations. Although HT-El is an innovative step in public service, regulatory harmonization is needed to provide legal certainty and protection for the parties involved. Recommendations in this study include legal reform, strengthening coordination between institutions, and establishing clear procedural standards to minimize risks in the electronic mortgage registration process.